Академічна культура українського студентства: фактори формування та особливості прояву - Пак, І.В.; Pak, I.V. (Харків: ХНУ імені В. Н. Каразіна, 2019)
Pak I.V. Academic culture of Ukrainian students: factors of formation and features of manifestation. – Qualification research paper, manuscript. Thesis for a Candidate Degree in Sociology: Speciality 22.00.04 – Special and Branch Sociologies (Sociology). – V. N. Karazin Kharkiv National University, the Ministry of Education and Science of Ukraine, Kharkiv, 2019. The dissertation contains theoretical and empirical analysis of the phenomenon of academic culture of students. The dissertation contains a thorough analysis of the identified scientific issues and the author's definition of academic culture, clarification of its levels and structure, an original vision of functions inherent in academic culture. The empirical basis of the dissertation is the results of nationwide survey «Ukrainian Students' Academic Culture: The Main Factors of Formation and Development»; international survey «TALIS», based on unformalized in-depth interviews. The author notes that the phenomenon of academic culture in the modern scientific discourse is analyzed from several points of view, which form a rather broad theoretical spectrum. Its extreme positions can be considered its relation (even identification) with organizational culture in the conditions of globalization and the definition of a special mission of higher education in the modern information society. The analytical approach of P. Bourdieu is used to interpret academic culture as a set of academic practices, which include as formal manifestations of academic culture, as well as informal academic practices. The academic culture of students is determined the as a set of behavior patterns, which are formed in the academic environment in the process of adaptation to the value-normative component of the education space, are internalized and find manifestation in everyday academic practices.
Academic culture of Ukrainian students: factors of formation and features of manifestation
У дисертації представлено результати аналізу феномену академічної культури студентства. Дисертація містить авторські визначення академічної культури, її функцій, уточнення її рівнів та структури. Емпіричною базою є результати дослідження «Академічна культура українського студентства: основні чинники формування та розвитку», міжнародного дослідження «TALIS», авторського дослідження, що ґрунтувалося на неформалізованих глибинних інтерв’ю. Застосовано аналітичний підхід П. Бурдьє для інтерпретації академічної культури як набору академічних практик. Визначено академічну культуру студентства як сукупність моделей поведінки, що формуються в академічному середовищі в процесі адаптації до ціннісно-нормативної складової освітнього простору, інтеріоризуються особистістю та знаходять прояв у повсякденних академічних практиках. У роботі встановлено та проаналізовано фактори, що зумовлюють особливості прояву вітчизняної академічної культури на макро-, мезо- та мікрорівнях. Операціоналізовано поняття «академічна культура», визначено її емпіричні індикатори. Розглянуто фактори, які впливають на формування академічної культури українських студентів, насамперед їхня освітньо-професійна мотивація. Представлено інтерпретацію таких понять, як «академічні практики», «академічна доброчесність» та «академічна недоброчесність».
Keywords: Research Subject Categories::SOCIAL SCIENCES; академічна культура; академічна доброчесність; академічна недоброчесність; студентство; повсякденні практики; формальні та неформальні практики; академічна культура студентів; суб'єкти академічної культури; academic culture; academic integrity; academic dishonesty; students; educational research; formal and informal practices; academic culture of students; subjects of academic culture